Production of methylmercury by sulphate-reducing bacteria in sediments from the orbetello lagoon in presence of high macroalgal loads - Pepi, Milva; Leonzio, Claudio; Focardi, Silvano E.; Renzi, Monia (Ecological Questions, 2020)
Methylmercury is a potent neurotoxin affecting shallow-water ecosystems. Mercury polluted sediment samples were collected at six different sites in the Orbetello Lagoon (central Italy) characterized by high levels of silt, iron, manganese hydroxides, and organic matter originated the latter originated from the decomposition of macroalgae. Porous water pointed out the presence of sulphates, methylmercury, and sulphides. Slurries arranged in anaerobic conditions from sediment aliquots from the six sites, with the addition of ionic mercury, highlighted the production of methylmercury. Sulphate reducing bacteria (SRB) were quantified in lagoon sediments; furthermore, sediments cultured under anaerobic conditions showed SRBs active in mercury methylation. Anaerobic cultures of SRB, amended with ionic mercury, produced methylmercury during the growth of bacterial cells. The percentage of aerobic mercury resistant bacteria was pointed out at each sampling site, evidencing the presence of bioavailable mercury. Several aerobic mercury resistant bacteria were isolated and their level of resistance to inorganic and organic forms of mercury was evaluated. These isolates may be potentially used for eventual bioremediation processes. Mercury methylation by SRB in the Orbetello Lagoon sediments was described for the first time, focusing the attention on the need for possible bioremediation processes by using autochthonous mercury resistant bacteria. Moreover, the influence of algal biomass on mercury methylation was highlighted for the first time in this lagoon ecosystem. The importance of removing algal biomass, as it represents a source of organic matter favouring the process of mercury methylation, was strongly pointed out in this study.